(untitled) (International Conference on Computers in Education, 2013)
Twitter is a very famous communication tool. We focused on Twitter as a platform of a response system to collect comments of audience about a presentation. We have developed a system that automatically generates a responsive environment about the presentation using various input and output interface. In this paper, we describe the outline of our system and the performance validation of our system.